Microclimatic analysis of mangroves in two distinct categories of Protected Areas and conserved status - Lima, Nádia Gilma Beserra De; Cunha-lignon, Marília [UNESP]; Galvani, Emerson (Editora da Universidade Federal de Uberlândia - EDUFU, 2021)
Mangrove forests provide essential ecosystem services to human communities, including climate regulation. In Brazil, the National System of Nature Conservation Units divides Protected Areas (PAs) into two categories: Full Protection (FP) and Sustainable Use (SU). The FP areas are composed of five categories, including National Parks, and the SU areas comprise seven categories, such as Environmental Protection Areas. The current research compared climatic attributes, leaf area index, and vegetation structure development in mangrove forests in two distinct categories of PAs (FP and SU) along the southern coast of the state of São Paulo (Brazil) to analyze the climatic conditions in different PA categories. A survey of the microclimatic attributes found that the conserved mangroves in the FP PA presented a) greater thermal stability in terms of the maximum, minimum, and mean air temperatures, and b) a better role of mangrove vegetation in (re)distributing the energy inside the forest. Therefore, it is affirmed that FP PAs play a fundamental role in maintaining the good conservation status of mangroves and, consequently, stabilizing the microclimate.
Keywords: Climatic attributes; Monitoring; Microclimate; Sustainable Use; Full Protection